Realias of the Soviet Union Period: Peculiarities of Their Reproduction in the German Translations of the Essays of Yu. Andrukhovych - Tkachivska, M.; Solyuk, M. (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
The article deals with the problem of reproduction of totalitarian period’s realias viewing scientific investigations concerned. Their classification and ways of translation are given. The study is based on Yu. Andrukhovych’s essays translated in German. The conclusion highlights findings concerning the methods of translation used by the interpreters.